2019
DOI: 10.1101/583443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breast cancer classification based on proteotypes obtained by SWATH mass spectrometry

Abstract: Accurate breast cancer classification is vital for patient management decisions, and better tumour classification is expected to enable more precise and eventually personalized treatment to improve patient outcomes. Here, we present a novel quantitative proteotyping approach based on SWATH mass spectrometry and establish key proteins for breast tumour classification derived from proteotype data. The study was based on 96 tissue samples representing five breast cancer subtypes according to conventional classifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Half of them was lymph node negative and half lymph node positive. From the panel of the key proteins presented in Table , SWATH‐MS assays were available for COMT, ERP29, RPN1, NB5R1, ADT2, and KTN1 in an assay library containing 4562 proteins (FDR < 0.01) . We compared levels of these proteins in 8 lymph node positive versus 8 lymph node negative primary tumors and confirmed higher level of COMT in lymph node positive TNBC tissues compared to their lymph node negative counterparts (FC = 2.34, p = 0.028, Table A).…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…Half of them was lymph node negative and half lymph node positive. From the panel of the key proteins presented in Table , SWATH‐MS assays were available for COMT, ERP29, RPN1, NB5R1, ADT2, and KTN1 in an assay library containing 4562 proteins (FDR < 0.01) . We compared levels of these proteins in 8 lymph node positive versus 8 lymph node negative primary tumors and confirmed higher level of COMT in lymph node positive TNBC tissues compared to their lymph node negative counterparts (FC = 2.34, p = 0.028, Table A).…”
Section: Resultsmentioning
confidence: 69%
“…To validate the changes of DSC1 using human tumor samples, we performed an IHC verification of DSC1 levels in the set of 96 breast cancer tissue samples . After a successful antibody test on specificity (Figure S4, Supporting Information), we showed that DSC1 level was significantly increased in lymph node positive versus negative luminal A grade 1 tumors ( p = 0.004 based on histoscore, Figure E), significantly increased in grade 3 versus grade 1 tumors ( p = 0.002) specifically in lymph node negative tumors ( p = 4e −5 ) but not in lymph node positive ones ( p = 0.828), and also increased in HER2 + versus HER2 − tumors ( p = 0.045, Figure E), see also Figures S5–S7, Supporting Information, for detailed data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations